Efek tinggi hisap terhadap kapasistas pompa sentrifugal - Tando, Arjal; Linrung, Alimuddin; Syafrun, Muhammad; Efendi, Rustam (Universitas Muhammadiyah Metro, 2024)
Centrifugal pumps are one type of pump commonly used in the industry, particularly in the processing and distribution of clean water. The characteristics of these pumps can be determined by varying the flow rate at a certain height. A study was conducted to investigate the effects of three different pump heights (3.5 m, 4.5 m, and 5.5 m) on the efficiency of a centrifugal pump using water at a temperature of 31℃. The results showed that the maximum overall efficiency was obtained at a height of 4.5 m with a value of 33.22% and a total head of 23.39 m. The pump height was found to have an impact on the pump capacity, with higher pump positions resulting in an increased occurrence of cavitation bubbles in the suction pipe, leading to a decrease in pump performance. Therefore, the placement of centrifugal pumps should be carefully considered, taking into account factors such as height and distance of the suction pipe, to minimize cavitation and achieve optimal pump performance.